Activation of the serotonergic 5-HT1A receptor in the paraventricular nucleus of the hypothalamus inhibits water intake and increases urinary excretion in water-deprived rats - Villa, Patricia de Souza [UNESP]; Menani, José Vanderlei [UNESP]; Pavan de Arruda Camargo, Gabriela Maria [UNESP]; Arruda Camargo, Luiz Antonio de [UNESP]; Saad, Wilson Abrao [UNESP] (Elsevier B.V., 2008)
The paraventricular nucleus (PVN) may be considered as a dynamic mosaic of chemically-specified subgroups of neurons. 5-HT1A is one of the prime receptors identified and there is expressed throughout all magnocellular regions of the PVN. Several reports have demonstrated that a subpopulation of the magnocellular neurons expressing 5-HT1A receptors are oxytocin (OT) neurons and activation of 5-HT1A receptors in the PVN increases the plasma OT. Increasing evidence shows that OT inhibits water intake and increases urinary excretion in rats. The aim of this study was to investigate the role of serotonergic 5-HT1A receptors in the lateral-medial posterior magnocellular region of the PVN in the water intake and diuresis induced by 24 h of water deprivation. Cannulae were implanted in the PVN of rats. 5-HT injections in the PVN reduced water intake and increased urinary excretion. 8-OH-DPAT (a 5-HT1A agonist) injections blocked the water intake and increased urinary output in all the periods of the observation. pMPPF (a 5-HT1A antagonist) injected bilaterally before the 8-OH-DPAT blocked its inhibitory effect on water intake and its diuretic effect. We suggest that antidipsogenic and diuretic responses seem to be mediated via 5-HT1A receptors of the lateral-medial posterior magnocellular region of the PVN in water-deprived rats. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: PVN; Water intake; Urinary excretion; 5-HT; 8-OH-DPAT; pMPPF